2016
DOI: 10.2215/cjn.08660815
|View full text |Cite
|
Sign up to set email alerts
|

Age and Outcomes Associated with BP in Patients with Incident CKD

Abstract: Background and objectives Hypertension is the most important treatable risk factor for cardiovascular outcomes. Many patients with CKD are elderly, but the ideal BP in these individuals is unknown.Design, setting, participants, & measurements From among 339,887 patients with incident eGFR,60 ml/min per 1.73 m 2 , we examined associations of systolic BP (SBP) and diastolic BP (DBP) with all-cause mortality, incident coronary heart disease (CHD), ischemic strokes, and ESRD from the time of developing CKD until t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
59
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 44 publications
3
59
1
7
Order By: Relevance
“…This study (12) identified an increased risk of mortality with lower diastolic BP (DBP; DBP,60 mmHg) but no association between higher levels of DBP (.80 mmHg) and examined outcomes; this finding is consistent with previous work by Kovesdy et al (13) and our group (14). The risk of isolated systolic hypertension increases as eGFR declines, and lower levels of DBP have been associated with increased risk of mortality and cardiovascular events (3,(15)(16)(17).…”
supporting
confidence: 90%
See 4 more Smart Citations
“…This study (12) identified an increased risk of mortality with lower diastolic BP (DBP; DBP,60 mmHg) but no association between higher levels of DBP (.80 mmHg) and examined outcomes; this finding is consistent with previous work by Kovesdy et al (13) and our group (14). The risk of isolated systolic hypertension increases as eGFR declines, and lower levels of DBP have been associated with increased risk of mortality and cardiovascular events (3,(15)(16)(17).…”
supporting
confidence: 90%
“…In a previous study of older adults with CKD, we also described a U-shaped relationship between SBP and mortality (increased risk of mortality with SBP.140 and ,130 mmHg compared with 130-139 mmHg) among adults ages 65-70 years old but found no increase in risk of death at higher levels of SBP for those ages $70 years old (14). In our previous analysis (14) and in this study (12), there was not a definitive increase in the relative risk of mortality for adults ages $80 years old when SBP was 140-149 or 150-159 mmHg (confidence intervals included unity). Kovesdy et al (12) expanded on this, however, via a more finely stratified analysis of higher SBP levels, which found an increase in relative risk of death even among those $80 years old when SBP was .160 mmHg.…”
supporting
confidence: 65%
See 3 more Smart Citations